Analisis Kerjasama Program Studi BKPI untuk Mewujudkan Proyek Independen Mahasiswa pada Merdeka Belajar Kampus Merdeka - Fadila, Fadila; Febriansyah, Febriansyah; Yanuarti, Eka; Hariansyah, M.; Fatimah, Siti (Institut Agama Islam Negeri Curup, 2024)
This research investigates the form of collaboration between the Counseling Guidance and Psychology Study Program (BKPI) to realize independent student projects, as well as describing partner institutions' perceptions of the opportunities and challenges of the BKPI Study Program in this context. Using mixed research methods, a qualitative approach is used to understand the form of collaboration and perceptions of institutions, while a quantitative approach is used to analyze the level of BKPI collaboration in student independent projects. Questionnaire results from schools show a high level of agreement with various forms of collaboration, such as field practice (77% strongly agree), research (70% strongly agree), and field studies (71% strongly agree). The institution's perception shows that the BKPI Study Program has significant opportunities to create jobs and transfer new knowledge to students, but also faces challenges such as the diverse cultural backgrounds of clients and a lack of understanding of educational science. In the context of independent projects, the BKPI Study Program is recognized as having great potential to make a positive contribution, especially in career opportunities and the implementation of theoretical knowledge in the world of work. However, challenges such as the diverse cultural backgrounds of clients and the complexity of the problems faced represent areas that need to be considered in developing student independent projects in the BKPI field.